If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + (-1n) = -7 Solving -3 + (-1n) = -7 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + (-1n) = -7 + 3 Combine like terms: -3 + 3 = 0 0 + (-1n) = -7 + 3 (-1n) = -7 + 3 Combine like terms: -7 + 3 = -4 (-1n) = -4 Divide each side by '-1'. n = 4 Simplifying n = 4
| x^2-4x+9=2 | | 3x^2+40x-2000=0 | | 2=4+(-2p) | | 13-2b=1 | | 1200=18(5t-1.5) | | 8=2-(-2t) | | 15ab+[(6ab-c)+(4ab+c)]= | | 8=2-(-2) | | M=-1/2;(-3,0) | | M÷-1/2;(-3,0) | | 6=3r-(-3) | | 2-(-3p)=11 | | r/3-2=1 | | 2/3u-3/2=-1/5 | | 14=4k+2 | | v(v)+3v-18=0 | | 10(x-2)/5x-10 | | 3(4x+6)=9x+122 | | (5u-4)(3-u)=0 | | -6(c+1)-(6+5c)= | | (2x+3)+(4x+8)=180 | | =(y+6u)(7y-7u-5) | | -12x-20=-10x-15 | | -2x-10=3x-15 | | fn=5n+6 | | 16x-10+9=99-30x | | 6cosx+5=-5cosx+14 | | x+.05x=252000 | | (6x-5)(8x+3)=0 | | 187=-x+8 | | x+.05x=456 | | x+.05x=110 |